Nutritional values of Apocyclops dengizicus (Copepoda: Cyclopoida) fed Chaetocerous calcitrans and Tetraselmis tetrathele - Omidvar, Farhadian; Md Yusoff, Fatimah; Mohamed, Suhaila (Wiley-Blackwell, 2009)
The cyclopoid copepod Apocyclops dengizicus was isolated from a marine shrimp pond, Penaeus monodon, Kuala Selangor, Malaysia, and reared in the laboratory for 3 months to establish a pure population stock. Amino acids and fatty acids of A. dengizicus were determined when fed Chaetocerous calcitrans (C), Tetraselmis tetrathele (T) and their combination (CT) (1:1 by number). The protein contents in A. dengizicus that received C, T and CT were 46.8%, 60.5% and 55.3% of dry weight respectively. Correspondingly, the lipid was 19.0%, 17.8% and 19.1% of dry weight for C,T and CT respectively. TheA. dengizicus cultured on C, T and CT had total essential amino acids without tryptophan measurement of 57.1, 60.3 and 67.8 and total non-essential amino acids of 42.9%, 40.0% and 32.2% of total amino acids. The fatty acid content of A. dengizicus showed that it was able to synthesize docosahexenoic acid (22:6n-3, DHA), eicosapentaenoic acid (20:5n-3, EPA) and arachidonic acid (20: 4n-6, ARA) from examined microalgal diets. The DHA:EPA:ARA ratios of A. dengizicus fed on C, T and CT were 6.8:3.0:1, 14.0:5.8:1 and 11.6:2.6:1 respectively. Apocyclops dengizicus could be suitable live food for larval ¢sh and shrimp rearing because it meets their nutritive requirements.